Stacked wire-mesh monoliths for VOCs combustion: Effect of the mesh-opening in the catalytic performance - Sanz, Oihane (2017)
Structured reactors based on low cost metallic wire-mesh substrates of highly enhanced transport properties can be an interesting alternative to parallel channel monolithic reactors. In this work stacked wire-mesh monoliths were studied for volatile organic compounds elimination. Monoliths of different mesh-opening were homogeneously and adherently dip-coated with Pt/Manganese Octahedral Molecular Sieve (OMS-2) bifunctional catalyst. The catalytic activity was tested in toluene and methanol complete oxidation reactions. Catalytic activity increases using stacked wire-mesh monoliths instead of parallel channel monoliths and decreases when increasing the wire-mesh opening, showing the importance of the mass-transfer phenomena (contact between the gas phase and the solid catalyst).